The effect of Chamfer to the Tensile Strength of Steel Jis S45cr Friction Welding Joints - Iis Siti Aisyah (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2016)
Friction welding is a joining process that utilizes the force of pressure and heat from the friction to melt the tip of the workpiece in order to be connected The research has been conducted to measure the influence of the length of one side chamfer to the characteristic of the tensile strength of steel JIS45Cr friction welding joints.The research was conducted by experimental method with rotation speed 1800 rpm, time kept at 50 seconds, load used was 3.5 kg, chamfer angle was 30º and the length chamfer were 3 mm, 5 mm, 7 mm, 9 mm and 11 mm. The tensile test conducted to find the effect of the chamfer length.The result of the research concluded that the highest tensile test on length variant of 7 mm, it was 97.3505 kN/mm2 and the lowest on 3 mm was 92.9868 kN/mm2. It is proved that the chamfer length effect to thee tensile strength of friction welding.